WOKÓŁ PRZESTRZENI NATURY: SUBSTYTUTY KULTUROWE JAKO NARZĘDZIE TWORZENIA PRZESTRZENI ŻYCIOWEJ CZŁOWIEKA - Dereniowska, Małgorzata (Pracowania Humanistycznych Studiów Interdyscyplinarnych WFPiK UAM, 2011)
This paper is an interdisciplinary approach to issue of the human experience of space. Originally human has been experiencing the space of Nature, looking for a soul in all the forms of Nature. If we take the space of a human into a consideration then an intuition appears that it is a part of the space of Nature. Human is one of the species coexisting in the earthly environment. Unlike the non-human beings, a man has an unique capability and possibility of converting his living space. From the ecological crisis point of view, the human does it by negatively affecting the space of Nature, which is the living space of other species. This destabilize the balance of the physicochemical parameters, decreasing the capacity of the environment. This leads to the thesis that human decreases the space of Nature, creating instead its cultural substitutes of the living space (one of the most typical is the virtual reality, Internet). When a human is living in industrial areas then he has the ability to fulfill himself in many planes he created. This allows to state a conclusion that because of the cultural substitutes the process of the destruction of the environment remains relatively unnoticed. As a consequence, the human may notice the ecological crisis later. Without the system motivating to change the way human acts in the area of cultural space the change seems to be improbable. It is possible to make it on the ethical and axiological level.
The space of Nature: cultural substitutes as tools for creating human's living space
Keywords: Kryzys ekologiczny; Ecological crisis; Natura; Nature; Substytucja; Substitution; Kultura; Culture